Fabrication and characterization of a wrist-driven rotational energy harvester using multiple plucked piezoelectric unimorphs. (November 2019) - Halim, M A; Xue, T; Rantz, R; Zhang, Q; Gu, L; Yang, K; Roundy, S
Abstract: We present fabrication and characterization of a wrist-worn rotational energy harvester using plucked piezoelectric unimorph beams for wearable applications. It consists of an eccentric rotor containing multiple magnets (at certain angular distance) and multiple unimorph beams (clamped to a central hub) with a magnet at the tip of each beam, in an in-plane plucking configuration. While excited, the unimorph beams are asynchronously plucked by the rotor magnets that generate voltage/power by means of the piezoelectric effect. An electromechanical model has been developed to predict the system performance for different plucking magnet configurations. The unimorph beams (12 mm×3.5 mm) are fabricated by bonding a 25 μm thick nickel (Ni) foil to a 43 μm thick lead zirconate titanate (PZT). In order to achieve the highest yield (~ 91%), a custom fabrication process has been developed that utilizes process steps both inside and outside the cleanroom. Finally, a prototype has been assembled and tested by mounting it on a custom-built driven pendulum to provide a controlled pseudo-walking excitation. The system shows non-linear behaviour with the change in the number of adjacent plucking magnets. The most frequently plucked beam generates a maximum of 6.25 μW average power while plucked by a three-magnet configuration under ±25° and 1.25 Hz pseudo-walking excitation. Experimental results are in good agreement with the simulation.